English teachers’ perspectives on the implementation of extensive reading - Maharani, Suci (Lililacs Journal, 2023)
There needs to be more literature regarding English teachers' perspectives on the actual practice of extensive reading in the classroom in Indonesia. Therefore, a study aimed to investigate the implementation of extensive reading based on the teachers' perspectives. This study employed a qualitative research method as the research design. The participants were two senior high school English teachers and two junior high school English teachers. Interviews were conducted as the data collection and transcribed for the data analysis. The results showed that all English teachers had acknowledged and were well-informed of the benefits of extensive reading. However, half of them projected their positive beliefs through implementing extensive reading in their teaching practice, but the other half did not. The obstacles found in applying extensive reading were the students' need for more interest in reading, their lack of vocabulary mastery, and opposing views toward reading. Therefore, this insight into the study's results has enriched the literature, and the stakeholder of the curriculum should provide support regarding the teachers' concern about implementing extensive reading. Keywords: perspective, implementation, extensive reading